2014
DOI: 10.1186/2040-7378-6-7
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin (IVIg) provides protection against endothelial cell dysfunction and death in ischemic stroke

Abstract: BackgroundThe brain endothelium is a key component of the blood brain barrier which is compromised following ischemia, allowing infiltration of damaging immune cells and other inflammatory molecules into the brain. Intravenous immunoglobulin (IVIg) is known to reduce infarct size in a mouse model of experimental stroke.FindingsFlow cytometry analysis showed that the protective effect of IVIg in ischemia and reperfusion injury in vivo is associated with reduced leukocyte infiltration, suggesting an involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Endothelial cells are key components of the BBB and are essential to neovascularization and maintenance of BBB integrity, but these functions are compromised after stroke. Treatment to attenuate BBB dysfunction may help to improve neurologic outcomes and facilitate recovery (Widiapradja et al, 2014). Here, we found that GFAP + or CD31 + cells were more abundant in eGFP + cells from the CXCR4 + CD45 − BMMNC-treated group than in those from mice treated with unfractionated BMMNCs.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells are key components of the BBB and are essential to neovascularization and maintenance of BBB integrity, but these functions are compromised after stroke. Treatment to attenuate BBB dysfunction may help to improve neurologic outcomes and facilitate recovery (Widiapradja et al, 2014). Here, we found that GFAP + or CD31 + cells were more abundant in eGFP + cells from the CXCR4 + CD45 − BMMNC-treated group than in those from mice treated with unfractionated BMMNCs.…”
Section: Discussionmentioning
confidence: 99%
“…IVIg has been previously shown to attenuate the activity of complement system, the expression of adhesion molecules, the expression and activation of inflammasome components, the induction of pro-inflammatory and apoptotic gene and protein expression and the production of cytokines (Arumugam et al, 2008: Arumugam et al, 2009Fann et al, 2013;Widiapradja et al, 2014;Lok et al, 2015). Our group has previously demonstrated that IVIg treatment protects against ischemic strokeinduced brain damage and neurological deficit in a mouse model of ischemia and reperfusion Widiapradja et al, 2012) by targeting the activation of the complement cascade and inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IVIg can directly protect neurons against ischemic conditions by targeting inappropriately activated components of the innate immune system, such as the complement system and the toll like receptors (TLRs) Lok et al, 2015), and it can also protect brain endothelial cells from death (Widiapradja et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, our objective was to characterise an in vitro OGD model using a mouse immortalised cerebral microvascular endothelial cell line, bEnd.3. This cell line has previously been used in OGD studies . However, the time of OGD (and RO) exposure used in these studies varies greatly, making it difficult to ascertain which conditions best simulate the key features of BBB disruption in vivo.…”
Section: Introductionmentioning
confidence: 99%